The Republican Command : 1897-1913 - Merrill, Horace Samuel (Book collections on Project MUSE., 1971)
This powerful book reminds us of the enormous power the nation accords its political leaders and how in the significant period, 1897--1913, these leaders failed to meet their responsibilities. Their inadequacies, the authors feel, delayed the administration of justice for all citizens, neglected the Negro, and seriously impaired the future effectiveness of their own once viable, successful, and justly proud Republican Party. The authors follow the maneuvers of McKinley, Roosevelt, Taft, Senators Aldrich, Platt, Allison, and Spooner, and House Speaker ""Uncle"" Joe Cannon as they juggled pressin.